Effect of operating pressure and fuel moisture on net plant efficiency of a staged, pressurized oxy-combustion power plant. (August 2015) - Gopan, Akshay; Kumfer, Benjamin M.; Axelbaum, Richard L.
Highlights: Parametric Analysis of fuel-Staged, Pressurized Oxy-Combustion process. Combustion pressure increase, beyond 16 bar, does not lead to significant increase in plant efficiency. At low fuel-moisture, effect of moisture on plant efficiency is low. Beyond heat saturation point, increase in moisture drastically reduces efficiency. Abstract: The immediate need for a high efficiency and low cost carbon capture process has prompted the recent development of pressurized oxy-combustion. With an increase in combustion pressure, the dew point of the flue gas is increased, allowing for effective integration of the latent heat of flue gas moisture into the Rankine cycle. This increases the net plant efficiency and reduces costs. The Staged, Pressurized Oxy-Combustion (SPOC) process further enhances the efficiency and reduces costs by reducing the recycle of flue gas to near zero. Fuel staging and a novel boiler/burner design are used to control temperature and heat flux. Compared to a first generation oxy-combustion process, the SPOC process results in an increased net plant efficiency of about 6 percentage points. In this work, the effects of operating pressure and fuel moisture content on the net plant efficiency are discussed. It is shown that the effect of pressure is small for pressures higher than about 16 bar, while the effect of fuel moisture is quite significant. Net plant efficiency gradually decreases with increasing fuel moisture until the heat saturation value, beyond which additional latent heat cannot be integrated into the steam cycle and the efficiency reduction is more dramatic. The effect of slurry feeding of coal on plant efficiency is discussed.